Strengthening National Identity and Religious Moderation through Civic Engagement-Based Citizenship Education in Higher Education (A Dual Case Study at UIN Siber Syekh Nurjati Cirebon and Jambi University) (JED (Jurnal Etika Demokrasi), 2025)
Abstract. This study aims to: (1) describe students’ understanding of national identity and religious moderation at Universitas Jambi and UIN Siber Syekh Nurjati Cirebon; (2) explain the role of civic engagement as a bridge between national values and religious moderation within the dichotomy of religious-based and participatory social approaches in higher education; and (3) analyze the similarities and differences in civic engagement approaches within Citizenship Education curricula at both institutions. Employing a qualitative approach with a multiple case study design, data were collected through in-depth interviews, participatory observation, and document analysis. The data were analyzed using Miles and Huberman’s interactive model and Yin’s cross-case analysis framework. The findings reveal that students’ comprehension of national identity and religious moderation varies, influenced by academic background, social experience, and campus environment. At UIN Siber Syekh Nurjati, the Rumah Moderasi Beragama (House of Religious Moderation) plays a central role in promoting the integration of religious and national values, although tensions remain between students of general and religious study programs. Meanwhile, Universitas Jambi has established the Griya Moderasi Beragama dan Bela Negara (GMBBN), which fosters student civic engagement through multiethnic, intercultural, and social initiatives. Civic engagement effectively serves as a meeting point between religious and civic values. The Citizenship Education curriculum at UIN is more ideologically religious, while Universitas Jambi applies a more contextual and participatory approach. This study recommends strengthening the integration of civic engagement into the Citizenship Education curriculum to enhance students’ national identity and inclusive religious attitudes in multicultural higher education environments.